Religious Identity, Trust, Reciprocity, and Prosociality: Theory and Evidence - Sanjit Dhami; Mengxing Wei; Pavan Mamidi (Center for Economic Studies and ifo Institute (CESifo), 2022)
We use the trust and the dictator games to explore the effects of religious identity on trust, trustworthiness, prosociality, and conditional reciprocity within a beliefs-based model. We provide a novel and rigorous theoretical model to derive the relevant predictions, which are then tested in pre-registered lab-in-the-field experiments from villages in the Indian states of Bihar and Uttar Pradesh. We find strong evidence of religious identity effects in the beliefs, and the chosen actions, for Hindu and Muslim subjects. Priming has little effect on Hindu subjects but it enhances religious polarization in beliefs and actions among Muslim subjects. There is taste-based discrimination but no statistical discrimination. All our underlying assumptions on beliefs, and their dependence on priming and identity are confirmed by the data, identifying a precise beliefs-based mechanism for the effects of religious identity. More religious subjects expect greater prosociality/reciprocity and often are more prosocial/reciprocal.
Keywords: C91; D01; D84; D91; 330; religious identity; trust; trustworthiness; prosociality; priming; conditional reciprocity